Dostosowania polskich eksporterów artykułów rolno-spożywczych do warunków integracji z UE na przykładzie woj. warmińsko-mazurskiego - Kisiel, Roman; Babuchowska, Karolina (Adaptation of Polish Agri-Food Products Exporters in the Aspect of the EU Integration Process (on the Example of Warmia and Mazury Voivodship), 2005)
The integration of Poland with the European Union caused fear connected with mass inflow of agri-food products on Polish market from the rest of the European Union's counties. In fact after 1st May 2004 there has been an increase of Polish food export. Polish producers who want to strengthen their role at the EU's single market are obliged to adapt their products to Union requirements. Research done in Warmia and Mazury Region show that almost 1/3 of agri-food products' producers made indispensable changes just before joining Poland with the EU.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 420-424